Relationshipbetweenperiodontal findings and Behc¸et’s disease: a controlled study - Ayse Akman (Blackwell Synergy, 2007)
Background: Behc¸et’s disease (BD) is a chronic, relapsing, systemic vasculitis of unknown aetiology. The involvement of oral mucosal surfaces represents the onset feature of the disease in the majority of patients. Objective: The aim of this study was to evaluate the periodontal status of BD patients and then compare with recurrent aphthous stomatitis (RAS) patients and healthy controls. We also determined the relationship between the periodontal condition and the clinical severity of the disease in BD patients. Methods: Eighty-six patients with BD, 63 patients with RAS and 82 healthy subjects were included in the study. The periodontal status of all subjects was evaluated according to the community periodontal index of treatment needs (CPITN). BD patients were also assessed for clinical severity score (CSS) as described previously. Results: The mean CPITN were observed to be higher in BD patients (1.79 0.96) compared with RAS patients (1.22 0.87) and healthy controls (1.18 0.98) (po0.001). There was a positive association between CSS and CPITN (p50.017) in BD patients. Conclusion: Our results showed that periodondal status is worse in BD patients and associated with disease severity. We can speculate that periodontitis may induce a systemic inflammatory process that may contribute to the development and/or progression of BD.